2004
DOI: 10.1523/jneurosci.5186-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Synapses Depend on Hippocampal Estrogen Synthesis

Abstract: Estrogens have been described to induce synaptogenesis in principal neurons of the hippocampus and have been shown to be synthesized and released by exactly these neurons. Here, we have focused on the significance of local estrogen synthesis on spine synapse formation and the synthesis of synaptic proteins. To this end, we reduced hippocampal estrogen synthesis in vitro with letrozole, a reversible nonsteroidal aromatase inhibitor. In hippocampal slice cultures, letrozole treatment resulted in a dose-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
345
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(384 citation statements)
references
References 75 publications
35
345
1
3
Order By: Relevance
“…Because BDNF expression is highest at proestrus (54), the decrease in endogenous E2 with aging will lead to decreased BDNF expression and contribute to the loss of E2's beneficial effects. Additional related factors include the impact of ovarian E2 depletion on local estrogen synthesis in hippocampus, which was recently shown to be critical for hippocampal function (54).…”
Section: Discussionmentioning
confidence: 99%
“…Because BDNF expression is highest at proestrus (54), the decrease in endogenous E2 with aging will lead to decreased BDNF expression and contribute to the loss of E2's beneficial effects. Additional related factors include the impact of ovarian E2 depletion on local estrogen synthesis in hippocampus, which was recently shown to be critical for hippocampal function (54).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of estradiol on spine density and LTP were frequently shown by either using ovariectomized animals, which had been treated systemically with estradiol (Gould et al, 1990;Warren et al, 1995;Có rdoba Montoya and Carrer, 1997;Smith and McMahon, 2005;Kramár et al, 2009), by applying estradiol to acute slices of mostly male rats (Foy et al, 1999;Ito et al, 1999;Mukai et al, 2007;Kramár et al, 2009), or by using mixed hippocampal slice cultures from neonatal males and females (Murphy and Segal, 1996;Kretz et al, 2004;Mendez et al, 2011). Thus, the vast majority of studies do not consider the potential differences between males and females.…”
Section: Introductionmentioning
confidence: 99%
“…We have already demonstrated that hippocampal neurons are capable of synthesizing estradiol de novo (Wehrenberg et al, 2001;Prange-Kiel et al, 2003) and that hippocampus-derived estradiol is required for the maintenance of hippocampal synapses (Kretz et al, 2004). Letrozole, which is a nonsteroidal aromatase inhibitor and is commonly used in the therapy of breast cancer, reliably inhibits estradiol synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, recent data also indicated that OVX for 3 months, by which serum estrogen level were markedly decreased, did not affect estrogen level and Aβ plaque formation in the brains of AD model transgenic mice (APP23) overexpressing a mutant amyloid precursor protein transgene, but significantly decreased the brain estrogen level followed by Aβ plaque formation in APP23 mice with an aromatase gene knockout (Yue et al, 2005). In addition, it has been reported that reducing estrogen levels by blocking aromatase activity with letrozole, a reversible non-steroidal aromatase inhibitor, reduces the density of spines and synapses in hippocampal slice cultures (Kretz et al, 2004). These findings suggest that brain-derived estrogens, which are converted from C19 steroids by aromatase, have more important role in the Aβ clearance and the maintenance of neural environment than ovary-derived estrogens.…”
Section: Discussionmentioning
confidence: 98%